History of faulting in the Northern Hastings Block, southern New England Orogen. Issue 7 (2nd October 2016) - Yan, J.; Lennox, P.G.; Offler, R.
ABSTRACT: Brittle failure is common in the Devonian to Permian rocks in the Northern Hastings Block (NHB) and is manifested by faults of different orientation and kinematic histories, but the timing of fault movement is not well defined. In this study, faults in the NHB were analysed with the map pattern of cross-cutting faults used to estimate the relative time of movement and relationship to other faults. We defined five episodes of faulting or fault reactivation that affected the NHB. The Yarras Fault System on the southwestern side of the NHB and the Parrabel Fault and related faults on the eastern side of the NHB are the two major fault systems responsible for transporting and rotating the NHB in the late Carboniferous. Faults on the eastern, northeastern and northern part of Parrabel Dome started and stopped moving after emplacement of the Hastings Block and before the intrusion of the Werrikimbe Triassic granitoids. We suggested that the movement on the major bounding faults is related to the accommodation of the NHB to the folding and cleavage development in the adjoining Nambucca Block, and is associated with the earliest part of the Hunter–Bowen Orogeny. Limited dextral movement on the extensions of the Taylors Arm Fault System caused minor displacements in the northeastern part of the NHB during the Late Triassic. Some small faults cut the Triassic granitoids or Triassic Lorne Basin sediments indicating tectonic activity continued post-Triassic.